Prevalence of indicators of low energy availability in elite female sprinters - Sygo, J.; Coates, A. M.; Sesbreno, E.; Mountjoy, M. L.; Burr, J. F. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
Low energy availability (LEA), and subsequent relative energy deficiency in sport, has been observed in endurance, aesthetic, and team sport athletes, with limited data on prevalence in athletes in short-burst activities such as sprinting. We examined prevalence of signs and symptoms of LEA in elite female sprinters at the start of the training season (PRE), and at the end of a 5-month indoor training period (POST). Four of 13 female sprinters (31%) presented at PRE testing with at least one primary (amenorrhea, low bone mineral density, low follicle-stimulating hormone, luteinizing hormone, or estradiol, resting metabolic rate =29 kcal/kg fat-free mass, Low Energy Availability in Females Questionnaire score =8) and one secondary indicator of LEA (fasting blood glucose <4 mmol/L, free triiodothyronine <3.5 pmol/L, ferritin <25 µg/L, low-density lipoprotein cholesterol >3.0 mmol/L, fasting insulin <20 pmol/L, low insulin-like growth factor-1, systolic blood pressure <90 mmHg, and/or diastolic blood pressure <60 mmHg). At POST, seven out of 13 athletes (54%) presented with at least one primary and one secondary indicator of LEA, three of whom had also presented with indicators of LEA at PRE. Five out of 13 (39%) athletes had previous stress fracture history, though this was not associated with current indicators of LEA (PRE: r =.52, p=.07; POST: r=-.07, p=.82). In conclusion, elite female sprinters may present with signs and symptoms of LEA, even after off-season rest. Medical and coaching staff should be aware of the signs and symptoms of LEA and relative energy deficiency in sport and should include appropriate screening and intervention strategies when working with sprinters.